Properties Chaotic of Rabinovich-Fabrvikant Equations (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
We give a new map named (Rabinovich-Fabrvikant equations) and  find five fixed points  we study only one fixed point  x0(0,0,0),  and  all general properties of them We prove  that the contracting and expanding  area of this point , thought the study of  the chaotic of  the point by use the Wiggins defined and we proof  that the lyapunov  exponent of the point  (0,0,0) is positive .We use matlab program to show sensitive dependence on the initial conditions and transitivity of (R-F).